Covıd-19 Bilgi Düzeyinin Sağlık Çalışanlarının Tutum Ve Davranışlarına Etkisi - Kılınç, Nur Özlem; Erci, Behice (Sivas Cumhuriyet Üniversitesi, 2022)
This cross-sectional study was conducted to determine the effect of healthcare workers’ COVID-19 knowledge level on their attitudes and behaviors. The population consisted of 1794 healthcare workers of a city hospital in Eastern Anatolia, Turkey. The study was conducted on a sample of 310 healthcare workers, as determined by power analysis, who were selected by accidental sampling. Data for the study were collected during February 2021 through a four-part online questionnaire that investigated sociodemographic characteristics, COVID-19 knowledge, attitudes towards COVID-19, and COVID-19-related behaviors. The average age of the participants was 34.50 ? 8.36 years, and the mean years of work experience was 11.94 ? 8.89. COVID-19 knowledge level was positively correlated with and explained 46% of variation in attitude towards COVID-19 and 28% of variation in COVID-19-related behaviors. We conclude that healthcare workers’ COVID-19 knowledge level positively affected their attitudes and behaviors towards COVID-19.

ÖZET Bu çalışma sağlık çalışanlarının bilgi düzeyinin tutum ve davranışlara etkisini belirlemek amacıyla yapılmıştır. Araştırma kesitsel bir araştırmadır. Araştırmanın evrenini Türkiye’nin Doğu Anadolu Bölgesinde bir Şehir Hastanesinde çalışan 1794 sağlık personeli, örneklemini ise güç analizi ile belirlenen 310 kişi oluşturmuştur. Evrenden örneklem seçiminde rastlantısal örneklem yöntemi kullanılmıştır. Araştırmanın verileri, Mart- Nisan tarihleri arasında dijital olarak toplanmıştır. Veriler dört bölümden oluşan bir anket kullanılarak toplanmıştır (sosyo-demografik özellikler, COVİD-19 hakkında bilgi, COVİD-19’ a yönelik tutumlar, COVID-19 ile ilgili davranışlar). Araştırmaya katılan sağlık çalışanlarının yaş ortalaması 34.50 ? 8.36 ve çalışma yıl ortalamaları 11.94 ? 8.89’dur. COVID-19 ile ilgili bilginin COVID-19 a karşı tutumu % 46 ve COVID-19 ile ilgili davranışları % 28 etkilediği görülmektedir. Bu çalışma ile sağlık çalışanlarının COVID-19 hakkındaki bilgi düzeylerinin, COVID-19 hakkındaki tutum ve davranışlarını olumlu yönde etkilediği belirlenmiştir.
The Effect Of Covid-19 Knowledge Level On Healthcare Workers’ Attitude And Beahavior
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi